Hydrophilic copolymers and hydrophilic compositions

By using specific aqueous copolymers in the aqueous coating, the problems of insufficient water resistance and degradation of anti-fog performance in the prior art are solved, and a coating with high water resistance and long-term anti-fog performance is achieved.

JP7661902B2Active Publication Date: 2025-04-15SHIN ETSU CHEMICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022006275
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-01-19
Publication Date
2025-04-15
Estimated Expiration
2042-01-19

AI Technical Summary

Technical Problem

In the prior art, the water-based coating used to improve the anti-fog performance of the substrate surface is not water-resistant enough, and the surface performance is easily degraded due to moisture, and may leave traces of water droplets after drying.

Method used

A specific aqueous copolymer is used that contains structural units (a) and (b) and forms a coating with high water resistance and long-term anti-fog properties through specific copolymerized structures and linkage groups (such as urea bonds, thiol bonds, etc.).

Benefits of technology

High water resistance and long-term anti-fog performance are achieved, so that the coating can maintain excellent surface performance after contacting moisture and avoid the appearance of water droplet traces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661902000001
    Figure 0007661902000001
  • Figure 0007661902000002
    Figure 0007661902000002
  • Figure 0007661902000003
    Figure 0007661902000003
Patent Text Reader

Abstract

To provide a hydrophilic copolymer that gives a coating film having excellent hydrophilicity, antifogging, and water resistance.SOLUTION: A hydrophilic copolymer comprises constituent units represented by formula (1) and formula (2) below (where, R1 and R3 each represent a hydrogen atom or a methyl group, R2's independently represent a hydrogen atom or a C1-6 alkyl group, R4 and R5 independently represent a C1-10 alkyl group or C6-10 aryl group, X1 and X2 each represent a divalent linking group, n is an integer of 1-3, and the asterisk (*) represents a bond to an adjacent constituent unit).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hydrophilic copolymer and a hydrophilic composition containing the same. [Background technology]

[0002] In recent years, there has been an increasing demand for improvement in the fogging of substrates made of organic materials such as plastics and inorganic materials such as glass. Improvement of the fogging of a substrate is generally achieved by forming a hydrophilic coating on the surface of the substrate. For example, Patent Document 1 proposes a coating composition containing a hydrophilic copolymer having a highly hydrophilic quaternary ammonium salt structure as a coating agent capable of imparting hydrophilicity to a substrate.

[0003] However, the coating film formed by the above-mentioned coating composition does not have sufficient water resistance, and after contact with water, the hydrophilic composition in the coating film may partially dissolve, resulting in deterioration of surface properties such as hydrophilicity and antifogging properties. Moreover, when such a portion dries, water drip marks may remain on the coating film. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-162431 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a hydrophilic copolymer which gives a coating film excellent in hydrophilicity, antifogging property and water resistance, and a hydrophilic composition containing the same. [Means for solving the problem]

[0006] Means for Solving the Problems The present inventors have conducted extensive research in order to achieve the above object and have found that a specific hydrophilic copolymer provides a coating film which is excellent in water resistance and can impart long-lasting hydrophilicity and anti-fogging properties to substrates formed of organic materials such as plastics and inorganic materials such as glass, thereby completing the present invention.

[0007] That is, the present invention provides 1. A hydrophilic copolymer comprising a structural unit (a) represented by the following formula (1) and a structural unit (b) represented by the following formula (2): [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, and R 2 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; X 1 represents a divalent linking group, In formula (2), R 3 represents a hydrogen atom or a methyl group, and R 4 and R 5 each independently represents an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 10 carbon atoms; X 2 represents a divalent linking group, n represents an integer of 1 to 3, and an asterisk * indicates a bond to an adjacent structural unit. 2. The above X 1 and X 2 each independently represents a divalent linking group having one or more bonds selected from the group consisting of a urethane bond, a urea bond, a thiourethane bond, and a thiourea bond; 3. A hydrophilic composition comprising the hydrophilic copolymer of 1 or 2, 4. A coating obtained by curing the hydrophilic composition of 3. to provide. Effect of the Invention

[0008] The hydrophilic copolymer of the present invention can provide a hydrophilic composition capable of forming a coating film having excellent water resistance and capable of imparting long-lasting hydrophilicity and anti-fogging properties to organic substrates such as plastics and inorganic substrates such as glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be specifically described below. [1] Hydrophilic copolymer The hydrophilic copolymer according to the present invention (hereinafter also simply referred to as "copolymer") contains the structural units (a) and (b) described below. Each of the constituent units of the hydrophilic copolymer according to the present invention will be described below. The structural unit (a) contained in the hydrophilic copolymer of the present invention is represented by the following formula (1).

[0010] [ka] (In the formula, the asterisk * has the same meaning as above.)

[0011] In formula (1), R 1 represents a hydrogen atom or a methyl group, with a hydrogen atom being preferred. R 2 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. R 2 The alkyl group having 1 to 6 carbon atoms may be linear, branched, or cyclic, and specific examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, and cyclohexyl groups. Among these, R 2 From the viewpoint of improving the hydrophilicity of the coating film, the alkyl group is preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and still more preferably a methyl group.

[0012] X 1 represents a divalent linking group. There is no particular limitation on this divalent linking group, but a divalent linking group having one or more bonds selected from the group consisting of a urethane bond, a urea bond, a thiourethane bond, and a thiourea bond is preferred, and -(CH2) k1 -Z-(CH2) k2A linking group represented by -(Z represents a urethane bond, a urea bond, a thiourethane bond or a thiourea bond, and k1 and k2 each independently represent an integer of 1 to 5, preferably an integer of 2 to 4) is more preferred. X 1 Specific examples of the divalent linking group include, but are not limited to, those represented by the following formulas:

[0013] [ka]

[0014] Specific examples of the structural unit (a) represented by the above formula (1) include those represented by the following formulae, but are not limited to these.

[0015] [ka] (In the formula, the asterisk * has the same meaning as above.)

[0016] The structural unit (b) contained in the hydrophilic copolymer of the present invention is represented by the following formula (2). The hydrolyzable silyl group contained in the structural unit (b) can undergo a crosslinking reaction with itself (self-crosslinking), thereby forming a crosslinked structure containing a hydrophilic copolymer in the coating film.

[0017] [ka] (In the formula, the asterisk * has the same meaning as above.)

[0018] In formula (2), R 3 represents a hydrogen atom or a methyl group, with a methyl group being preferred. R 4 and R 5 each independently represents an alkyl group having 1 to 10 carbon atoms, preferably 1 to 8 carbon atoms, and more preferably 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms, preferably 6 to 8 carbon atoms. R 4and R 5 The alkyl group may be linear, branched, or cyclic, and specific examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, s-butyl, t-butyl, n-pentyl, n-hexyl, and cyclohexyl groups. R 4 and R 5 Specific examples of the aryl group include phenyl and tolyl groups. Among these, R 4 is preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group; R 5 is preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group.

[0019] X 2 represents a divalent linking group. There is no particular limitation on this divalent linking group, but a divalent linking group having one or more bonds selected from the group consisting of a urethane bond, a urea bond, a thiourethane bond, and a thiourea bond is preferred, and -(CH2) k1 -Z-(CH2) k2 A linking group represented by -(Z represents a urethane bond, a urea bond, a thiourethane bond or a thiourea bond, and k1 and k2 each independently represent an integer of 1 to 5, preferably an integer of 2 to 4) is more preferred. X 2 Specific examples of the divalent linking group include, but are not limited to, those represented by the following formulas: Among these, those containing a urea bond represented by (3) are preferred.

[0020] [ka]

[0021] n represents an integer of 1 to 3, with 3 being preferred.

[0022] Specific examples of the structural unit (b) represented by the above formula (2) include those represented by the following formulas, but are not limited to these.

[0023] [ka] (In the formula, the asterisk * has the same meaning as above.)

[0024] In the hydrophilic copolymer of the present invention, the content of the structural unit (a) is preferably 50 to 99% by mass, more preferably 70 to 98% by mass, and even more preferably 90 to 97% by mass. If the content of the structural unit (a) is 50% by mass or more, the hydrophilicity of the copolymer is improved, and the coating film has excellent hydrophilicity when formed into a coating film. On the other hand, if the content of the structural unit (a) is 98% by mass or less, the hydrophilicity of the copolymer is not too high, and the coating film has excellent water resistance when formed into a coating film. The content of the structural unit (b) is preferably from 1 to 20 mass %, more preferably from 5 to 30%, and even more preferably from 5 to 15%. The total content of the structural unit (a) and the structural unit (b) in the hydrophilic copolymer of the present invention is preferably 51 to 100 mass%, more preferably 80 to 100 mass%, and even more preferably 90 to 100 mass%.

[0025] The hydrophilic copolymer of the present invention may contain, in addition to the above-mentioned structural units (a) and (b), a structural unit (c) represented by the following formula (4).

[0026] [ka] (In the formula, the asterisk * has the same meaning as above.)

[0027] In formula (4), R 6 represents a hydrogen atom or a methyl group, with a methyl group being preferred. X 3 represents -NH- or -O-, with -O- being preferred. Y 1 is a group selected from the group consisting of a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, an isocyanate group, an epoxy group, an alkoxy group (--OR), and a hydrolyzable silyl group. Y 1The alkoxy group (-OR) of R includes an alkyl group having 1 to 6 carbon atoms, which may be substituted or unsubstituted, and specific examples thereof include methoxy, ethoxy, n-propoxy, i-propoxy, n-butoxy, sec-butoxy, t-butoxy, n-pentyloxy, n-hexyloxy, cyclopentyloxy, cyclohexyloxy, etc. Some or all of the hydrogen atoms bonded to the carbon atoms of the alkyl group of R may be substituted with halogen atoms such as chlorine, fluorine, bromine, etc., or other substituents such as a cyano group. Y 1 Specific examples of the hydrolyzable silyl group include alkoxysilyl groups such as trimethoxysilyl, triethoxysilyl, dimethoxysilyl, diethoxymethylsilyl, monomethoxydimethylsilyl, and monoethoxydimethylsilyl groups; carboxylate silyl groups such as acetoxysilyl group; halosilyl groups such as trichlorosilyl, dichlorosilyl, and monochlorosilyl groups; aminosilyl groups; oximesilyl groups; and hydrosilyl groups. Among these, Y 1 is preferably a hydrogen atom or a hydroxyl group.

[0028] j is an integer of 0 to 10, preferably an integer of 0 to 6, more preferably an integer of 1 to 4, and further preferably an integer of 2 to 4. However, when j is 0, Y 1 is a hydrogen atom.

[0029] When the hydrophilic copolymer of the present invention contains the structural unit (c), for example, the copolymer of the present invention and the Y 1 When the copolymer of the present invention is used in combination with a curing agent having a functional group capable of crosslinking with the copolymer, a crosslinked structure can be formed between the curing agent and the copolymer. In addition, when the copolymer of the present invention is used in combination with a curing catalyst such as an acid catalyst, the copolymer itself can crosslink (self-crosslink). Therefore, the coating film formed from the composition containing the hydrophilic copolymer of the present invention and a curing agent has a crosslinked structure and can exhibit excellent water resistance.

[0030] From this point of view, in the above formula (4), Y 1is more preferably a hydroxyl group. 1 In the case where the copolymer of the present invention contains a structural unit (c) in which R is a hydroxyl group, for example, by combining the copolymer of the present invention with a curing agent having an isocyanate group, a crosslinked structure can be formed even under low temperature conditions (for example, 110° C. or lower). Therefore, a coating film can be formed from a composition containing the hydrophilic copolymer of the present invention even on a substrate having low heat resistance.

[0031] Specific examples of the structural unit (c) represented by the above formula (4) include those represented by the following formulas, but are not limited to these.

[0032] [ka] (In the formula, the asterisk * has the same meaning as above.)

[0033] When the hydrophilic copolymer of the present invention contains the structural unit (c), its content is not particularly limited, but is preferably 1 to 50 mass %, more preferably 3 to 20 mass %, and even more preferably 5 to 10 mass %.

[0034] The order of the respective structural units contained in the hydrophilic copolymer of the present invention may be arbitrary, and the copolymer of the present invention may be any of an alternating copolymer, a random copolymer, and a block copolymer.

[0035] The weight-average molecular weight of the hydrophilic copolymer of the present invention is not particularly limited, but from the viewpoint of improving the affinity with organic solvents and the hardness of the coating film, it is preferably 1,000 to 1,000,000, more preferably 5,000 to 700,000, even more preferably 300,000 to 600,000, and still more preferably 400,000 to 500,000. In the present invention, the weight-average molecular weight is a value measured by gel permeation chromatography (GPC) (standard substance: polystyrene, developing solvent: tetrahydrofuran).

[0036] Although there is no particular limitation on the viscosity of the hydrophilic copolymer of the present invention, from the viewpoints of compatibility with organic solvents and workability, it is preferably 0.01 to 0.5 Pa·s (temperature: 25° C.) In the present invention, the viscosity is a value measured using a B-type rotational viscometer. The glass transition temperature of the hydrophilic copolymer of the present invention is preferably −10 to 50° C. In the present invention, the glass transition temperature is a value measured based on JIS K7121.

[0037] The hydrophilic copolymer of the present invention can be obtained by a known method. For example, as shown in the scheme below, in the presence of a polymerization initiator, a polymerizable monomer containing an isocyanate group, as represented by the following formula (5), is polymerized under an inert gas atmosphere such as nitrogen, and then an aminoalcohol represented by the following formula (6) and an organosilicon compound represented by the following formula (7) are reacted with each other under an air atmosphere or an inert gas atmosphere such as nitrogen to obtain the hydrophilic copolymer.

[0038] [ka]

[0039] In the above formulas, R 1 ~R 5 , X 1 , X 2 and n have the same meaning as above, h represents an integer of 1 to 10, g represents an integer of 1 to 3, Y 2 represents a functional group selected from the group consisting of -NH(R'), -SH and -OH, R' represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and a, b and c are values ​​that result in the content of each structural unit falling within the above range. Examples of the alkyl group having 1 to 6 carbon atoms include the same as those mentioned above.

[0040] As the polymerizable monomer containing an isocyanate group of the above formula (5), a commercially available product may be used, for example, Karenz (registered trademark) AOI manufactured by Showa Denko KK and the like.

[0041] The polymerization initiator is preferably a thermal polymerization initiator, and the amount of the polymerization initiator added is preferably 0.5 to 30% by mass, more preferably 1 to 20% by mass, and even more preferably 2 to 10% by mass, based on the total mass of the monomers to be copolymerized. The polymerization initiator may be added all at once or in several portions.

[0042] Specific examples of the compound represented by the above formula (7) are shown below, but are not limited to these. Among these, the compound represented by (8) is preferred.

[0043] [ka] (In the formula, Me represents a methyl group, and Et represents an ethyl group.)

[0044] The above reaction can be carried out without a solvent, but can also be carried out in an organic solvent such as methyl ethyl ketone, 1,2-dimethoxyethane, etc., if necessary, so long as it does not inhibit the reaction. The reaction temperature is preferably from 0° C. to the boiling point of each solvent, and more preferably from 20 to 80° C. The reaction time is preferably from 1 to 24 hours, and more preferably from 5 to 10 hours.

[0045] The hydrophilic copolymer obtained by the above method may be mixed with additives after adjusting the solid content concentration, exchanging the solvent, or filtering, if necessary. The hydrophilic copolymer produced by polymerization may be purified by precipitation or reprecipitation with hexane or the like, and dissolved together with additives in a solvent according to the application.

[0046] [2] Hydrophilic composition The hydrophilic composition of the present invention (hereinafter, also simply referred to as "composition") contains one or more of the above hydrophilic copolymers. The content of the hydrophilic copolymer contained in the composition of the present invention is not particularly limited, but from the viewpoint of hydrophilicity, it is preferably 1 to 50 mass % of the total composition, more preferably 5 to 25 mass %.

[0047] The composition of the present invention may contain other additives, etc., within the scope of not impairing the object of the present invention. Other additives include acids such as hydrochloric acid, sulfuric acid, nitric acid, acetic acid, formic acid, oxalic acid, maleic acid, etc.; alkalis such as ammonia, methylamine, ethylamine, etc.; organic metal salts; Lewis acids; alkyl tin ester compounds; leveling agents; surfactants, etc. Among these, the addition of organic metal salts makes it possible to obtain a hydrophilic film that is hardenable at 25°C and 50% RH and has high durability.

[0048] The leveling agent and surfactant are contained in order to improve the uniformity of the coating film, and known agents can be used. Commercially available products are particularly preferred because they are easily available.

[0049] Examples of the organic metal salt include sodium acetate, potassium acetate, sodium propionate, potassium propionate, sodium formate, potassium formate, and tin octylate. Specific examples of Lewis acids include tetraisopropyl titanate, tetrabutyl titanate, aluminum triisobutoxide, aluminum triisopropoxide, aluminum acetylacetonate, tin chloride (SnCl4), titanium chloride (TiCl4), zinc chloride (ZnCl4), and the like. Specific examples of the alkyltin ester compound include alkyltin ester compounds such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin dioctoate, dioctyltin dioctoate, and dioctyltin diversatate. These may be used alone or in combination of two or more.

[0050] When the composition of the present invention contains an organometallic salt, the content thereof is preferably 0.05 to 50 parts by mass, more preferably 0.1 to 5 parts by mass, based on 100 parts by mass of the hydrophilic copolymer.

[0051] The composition of the present invention may contain a solvent, if necessary. The solvent is not particularly limited as long as it can dissolve or disperse the hydrophilic copolymer and other additives, does not react with each component, and can be easily removed in the drying step described below. Specific examples of the solvent include methanol, ethanol, isopropanol, tetrahydrofuran, cyclohexanone, methyl ethyl ketone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, 2-methoxyethyl acetate, diethylene glycol dimethyl ether, 1-methoxy-2-propanol, 1-methoxy-2-propyl acetate, N,N-dimethylformamide, N,N-dimethylacetamide, toluene, ethyl acetate, ethyl lactate, methyl lactate, dimethyl sulfoxide, and water. These may be used alone or in combination of two or more.

[0052] The solid content concentration of the composition of the present invention is preferably from 5 to 80% by mass, more preferably from 10 to 30% by mass, from the viewpoints of coatability and workability. The viscosity of the composition of the present invention is preferably 0.01 to 0.05 Pa·s (at 25° C.) from the viewpoints of coatability and workability. The composition of the present invention may be a one-liquid type, or may be a type in which two or more liquids are mixed before use.

[0053] The composition of the present invention can impart hydrophilicity to various substrates by applying it to the substrates. Specific examples of materials constituting the above-mentioned substrate include, for example, glass; synthetic resins {polymethyl methacrylate resin, polyethylene terephthalate resin, polybutylene terephthalate resin, polyethylene naphthalate resin, ABS resin, polycarbonate resin, polystyrene resin, epoxy resin, unsaturated polyester resin, melamine resin, diallyl phthalate resin, polyimide resin, urethane resin, nylon resin, polyethylene resin, polypropylene resin, polyvinyl chloride resin, fluororesins (polytetrafluoroethylene resin, polychlorotrifluoroethylene resin, polyvinylidene fluoride resin, perfluoroalkoxy fluororesin, tetrafluoroethylene-hexafluoropropylene copolymer resin, ethylene-tetrafluoroethylene copolymer resin, ethylene-chlorotrifluoro ethylene copolymer resins, etc.), polybutadiene, polyisopropylene, SBR, nitrile rubber, EPM, EPDM, epichlorohydrin rubber, neoprene rubber, polysulfide, butyl rubber, etc.}; metals (iron, aluminum, stainless steel, titanium, copper, brass, alloys thereof, etc.); cellulose, cellulose derivatives, cellulose analogues (chitin, chitosan, porphyran, etc.), natural fibers such as cotton, silk, wool, regenerated fibers such as rayon, semi-synthetic fibers such as acetate, synthetic fibers such as vinylon, polyester, nylon, polyethylene, polypropylene, polyurethane, polyaramid fibers, etc.; composite fibers of these fibers (polyester / cotton, etc.), and the like, and examples of the form of such fibers include substrates, sheets, films, fibers, and various articles using these.

[0054] The composition of the present invention can be applied onto the surface of a substrate or the like to form a coating film, which can be used as a hydrophilic coating film. Examples of the coating method include bar coating, dip coating, spin coating, spray coating, float coating, brush coating, gravure coating, roll transfer, blade coating, air knife coating, slit coating, screen coating, inkjet printing, and flexographic printing. Of these, bar coating is preferred.

[0055] After applying the composition onto a substrate, the composition is allowed to stand at room temperature in the atmosphere to obtain a cured coating film. The standing time is preferably 12 to 240 hours, more preferably 24 to 120 hours. Heat may also be applied to shorten the curing process. In this case, the heating temperature is preferably 40 to 250°C, and more preferably 80 to 120°C. The heating time is preferably from 10 seconds to 12 hours, and more preferably from 30 seconds to 3 hours. The heating atmosphere may be either an air atmosphere or an inert gas (eg, nitrogen, argon, etc.) atmosphere.

[0056] The thickness of the coating film (dry film thickness) is not particularly limited, but is preferably 0.1 to 50 μm, and more preferably 1 to 20 μm. EXAMPLES

[0057] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0058] (1) Preparation of hydrophilic copolymer [Example 1-1] Into a reactor, 102.16 g of 1,2-dimethoxyethane, 42.34 g of Karenz (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the following formula (9), and 1.44 g of an oil-soluble azo polymerization initiator V-59 (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) represented by the following formula (10) were added, and the mixture was reacted at 80° C. for 4 hours. Next, the heating of the reaction vessel was stopped, and after the temperature of the solution in the reaction vessel had dropped below 25°C, 24.74 g of 2-(dimethylamino)ethanol, 4.24 g of 3-aminopropyltrimethoxysilane, and 0.15 g of dioctyltin catalyst Neostan U-830 (manufactured by Nitto Kasei Co., Ltd.) were added, and the reaction was carried out at 25°C for 4 hours. After the reaction, the mixture was filtered to obtain 170 g of a 1,2-dimethoxyethane solution (solids concentration: 41% by mass) of hydrophilic copolymer P1 (content of structural unit (a) 92.5% by mass, content of structural unit (b) 7.5% by mass; weight average molecular weight 410,000).

[0059] [ka]

[0060] [Example 1-2] Into a reactor, 102.16 g of 1,2-dimethoxyethane, 42.34 g of Karenz (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 1.44 g of an oil-soluble azo polymerization initiator V-59 (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) represented by the above formula (10) were added, and the mixture was reacted at 80° C. for 4 hours. Next, the heating of the reaction vessel was stopped, and after the temperature of the solution in the reaction vessel had dropped below 25°C, 24.07 g of 2-(dimethylamino)ethanol, 5.65 g of 3-aminopropyltrimethoxysilane, and 0.15 g of dioctyltin catalyst Neostan U-830 (manufactured by Nitto Kasei Co., Ltd.) were added, and the reaction was carried out at 25°C for 4 hours. After the reaction, the mixture was filtered to obtain 170 g (solids concentration 41% by mass) of a 1,2-dimethoxyethane solution of hydrophilic copolymer P2 (content of structural unit (a) 90% by mass, content of structural unit (b) 10% by mass; weight average molecular weight 410,000).

[0061] [Examples 1-3] Into a reactor, 109.45 g of methyl ethyl ketone, 35.28 g of Karenz (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 1.20 g of an oil-soluble azo polymerization initiator V-59 (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) represented by the above formula (10) were added, and the mixture was reacted at 80° C. for 4 hours. Next, the heating of the reaction vessel was stopped, and after the temperature of the solution in the reaction vessel had dropped below 25°C, 20.61 g of 2-(dimethylamino)ethanol, 3.87 g of 3-mercaptopropyltrimethoxysilane, and 0.15 g of dioctyltin catalyst Neostan U-830 (manufactured by Nitto Kasei Co., Ltd.) were added, and the reaction was carried out at 25°C for 4 hours. After the reaction, the mixture was filtered to obtain 160 g (solids concentration 36% by mass) of a methyl ethyl ketone solution of hydrophilic copolymer P3 (content of structural unit (a) 92.5% by mass, content of structural unit (b) 7.5% by mass; weight average molecular weight 420,000).

[0062] [Examples 1-4] Into a reactor, 109.45 g of methyl ethyl ketone, 35.28 g of Karenz (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 1.20 g of an oil-soluble azo polymerization initiator V-59 (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) represented by the above formula (10) were added, and the mixture was reacted at 80° C. for 4 hours. Next, the heating of the reaction vessel was stopped, and after the temperature of the solution in the reaction vessel had dropped below 25°C, 20.06 g of 2-(dimethylamino)ethanol, 5.15 g of 3-mercaptopropyltrimethoxysilane, and 0.15 g of dioctyltin catalyst Neostan U-830 (manufactured by Nitto Kasei Co., Ltd.) were added, and the reaction was carried out at 25°C for 4 hours. After the reaction, the mixture was filtered to obtain 160 g (solids concentration 36% by mass) of a methyl ethyl ketone solution of hydrophilic copolymer P4 (content of structural unit (a) 90% by mass, content of structural unit (b) 10% by mass; weight average molecular weight 420,000).

[0063] [Examples 1-5] Into a reactor, 109.45 g of methyl ethyl ketone, 35.28 g of Karenz (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 1.20 g of an oil-soluble azo polymerization initiator V-59 (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) represented by the above formula (10) were added, and the mixture was reacted at 80° C. for 4 hours. Next, the heating of the reaction vessel was stopped, and after the temperature of the solution in the reaction vessel had dropped below 25°C, 20.06 g of 2-(dimethylamino)ethanol, 4.69 g of 3-aminopropyldimethoxymethylsilane, and 0.15 g of dioctyltin catalyst Neostan U-830 (manufactured by Nitto Kasei Co., Ltd.) were added, and the reaction was carried out at 25°C for 4 hours. After the reaction, the mixture was filtered to obtain 160 g of a methyl ethyl ketone solution (solid concentration 36% by mass) of hydrophilic copolymer P5 (content of structural unit (a) 90% by mass, content of structural unit (b) 10% by mass; weight average molecular weight 420,000).

[0064] [Comparative Example 1-1] Into a reactor, 109.45 g of methyl ethyl ketone, 35.28 g of Karenz (registered trademark) AOI (manufactured by Showa Denko K.K.) represented by the above formula (9), and 1.20 g of an oil-soluble azo polymerization initiator V-59 (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) represented by the above formula (10) were added, and the mixture was reacted at 80° C. for 4 hours. Next, the heating of the reaction vessel was stopped, and after the temperature of the solution in the reaction vessel had dropped below 25°C, 22.29 g of 2-(dimethylamino)ethanol and 0.15 g of dioctyltin catalyst Neostan U-830 (manufactured by Nitto Kasei Co., Ltd.) were added, and the reaction was carried out at 25°C for 4 hours. After the reaction, the mixture was filtered to obtain 160 g (solids concentration 36% by mass) of a methyl ethyl ketone solution of hydrophilic polymer P6 (content of structural unit (a) 100% by mass; weight average molecular weight 420,000).

[0065] [Comparative Example 1-2] Into a reactor, 44.02 g of ethyl acetate, 64.05 g of dimethylaminopropylacrylamide represented by the following formula (11), and 1.97 g of an oil-soluble azo polymerization initiator V-59 (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) represented by the above formula (10) were added, and the reaction was carried out at 80° C. for 4 hours. After the reaction, the mixture was filtered to obtain 100 g (solid content concentration: 48% by mass) of an ethyl acetate solution of hydrophilic polymer P7 (weight average molecular weight: 350,000).

[0066] [ka]

[0067] [Comparative Example 1-3] Into a reactor, 5.92 g of methanol, 1.41 g of dimethylaminopropylacrylamide represented by the above formula (11), 0.23 g of 3-acryloxypropyltrimethoxysilane represented by the following formula (12), and 0.77 g of oil-soluble azo polymerization initiator V-59 (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) represented by the above formula (10) were added, and the mixture was reacted at 65° C. for 4 hours. After the reaction, the mixture was filtered to obtain 7 g (solid content concentration: 25% by mass) of a methanol solution of hydrophilic copolymer P8 (weight average molecular weight: 400,000).

[0068] [ka]

[0069] (2) Preparation of coating composition (hydrophilic composition) [Example 2-1] A reactor was charged with 1.21 g of a 1,2-dimethoxyethane solution of the hydrophilic copolymer P1 obtained in Example 1-1, 0.79 g of isopropanol, and 0.02 g of titanium-based catalyst D-25 (Shin-Etsu Chemical Co., Ltd.), to obtain a yellow transparent liquid (C1).

[0070] [Example 2-2] Into a reactor, 1.21 g of a 1,2-dimethoxyethane solution of the hydrophilic copolymer P2 obtained in Example 1-2, 0.79 g of isopropanol, and 0.02 g of titanium-based catalyst D-25 (manufactured by Shin-Etsu Chemical Co., Ltd.) were added to obtain a yellow transparent liquid (C2).

[0071] [Example 2-3] Into a reactor, 1.39 g of a methyl ethyl ketone solution of the hydrophilic copolymer P3 obtained in Example 1-3, 0.61 g of isopropanol, and 0.02 g of titanium-based catalyst D-25 (Shin-Etsu Chemical Co., Ltd.) were added to obtain a yellow transparent liquid (C3).

[0072] [Example 2-4] Into a reactor, 1.39 g of a methyl ethyl ketone solution of the hydrophilic copolymer P4 obtained in Example 1-4, 0.61 g of isopropanol, and 0.02 g of titanium-based catalyst D-25 (Shin-Etsu Chemical Co., Ltd.) were added to obtain a yellow transparent liquid (C4).

[0073] [Example 2-5] Into a reactor, 1.39 g of a methyl ethyl ketone solution of the hydrophilic copolymer P5 obtained in Example 1-5, 0.61 g of isopropanol, and 0.02 g of titanium-based catalyst D-25 (manufactured by Shin-Etsu Chemical Co., Ltd.) were added to obtain a yellow transparent liquid (C5).

[0074] [Comparative Example 2-1] Into a reactor, 1.39 g of a methyl ethyl ketone solution of the hydrophilic polymer P6 obtained in Comparative Example 1-1 and 0.61 g of isopropanol were added to obtain a yellow transparent liquid (C6).

[0075] [Comparative Example 2-2] Into a reactor, 1.04 g of an ethyl acetate solution of the hydrophilic polymer P7 obtained in Comparative Example 1-2 and 0.96 g of isopropanol were added to obtain a yellow transparent liquid (C7).

[0076] [Comparative Example 2-3] Into a reactor, 2.00 g of a methanol solution of the hydrophilic copolymer P8 obtained in Comparative Example 1-3 and 0.02 g of titanium-based catalyst D-25 (Shin-Etsu Chemical Co., Ltd.) were added to obtain a yellow transparent liquid (C8).

[0077] [Comparative Example 2-4] In a reactor, 10 g of hydroxyl-containing acrylic resin ACRYL 6BF-100 (solid content concentration 40% by mass, manufactured by Taisei Fine Chemical Co., Ltd.) having a weight average molecular weight of 75,000, a hydroxyl value of 20 mgKOH / g, and a calculated glass transition temperature of 85 ° C., 0.65 g of Duranate TPA-100 (NCO content 23% by mass, manufactured by Asahi Kasei Co., Ltd.), 1.0 g of a methyl ethyl ketone solution (solid content concentration 40% by mass) of ACRYL 1WX (manufactured by Taisei Fine Chemical Co., Ltd.), which is a copolymer containing structural units represented by the following formulas (13), (14), (15), (16), and (17), and 13.6 g of methyl ethyl ketone were mixed to obtain a yellow transparent liquid (C9).

[0078] [ka] (In the formula, the asterisk * has the same meaning as above.)

[0079] (3) Preparation and evaluation of coating film [Examples 3-1 to 3-5, Comparative Examples 3-1 to 3-4] Each of the coating compositions C1 to C9 obtained in the above Examples 2-1 to 2-5 and Comparative Examples 2-1 to 2-4 was applied to a polycarbonate plate using a bar coater (No. 20), and then immediately dried at 120°C for 1 hour to obtain a hydrophilic coating.

[0080] [Examples 4-1 to 4-5, Comparative Examples 4-1 to 4-4] The coating compositions C1 to C9 obtained in the above Examples 2-1 to 2-5 and Comparative Examples 2-1 to 2-4 were each applied to a polycarbonate plate using a bar coater (No. 20), and left to stand for 24 hours in an environment of 25°C and 50% RH to obtain a hydrophilic coating.

[0081] The hydrophilic coatings prepared in the above examples were subjected to the following tests, and the results are shown in Tables 1 and 2. [Anti-fogging properties] Breath was blown onto each of the above coatings, and if the surface of the coating became cloudy, it was marked with an X, and if it did not become cloudy, it was marked with an O. Furthermore, the coating was placed above a 40°C warm water bath at a height of 3 cm above the water surface for 60 seconds, and if the surface of the coating did not become cloudy, it was marked with an ⊚ to evaluate the anti-fogging properties. [Water drip marks] In the above anti-fogging evaluation, the coating film was placed over a 40°C warm water bath for 60 seconds to evaluate the anti-fogging properties, and then naturally dried at 25°C for 10 minutes. The surface was then illuminated with a 1,000 lm flashlight and visually inspected to see if there were any traces of dripping water on the coating film surface. If there were any traces of dripping water, the rating was +, and if there were no traces, the rating was -. [Hot water resistance] Each of the above coating films was immersed in warm water at 40° C. for 24 hours, the water on the surface was wiped off with a paper wiper, and then the film was naturally dried at 25° C. for 10 minutes, and the above anti-fogging properties were evaluated. Next, each coating was further immersed in warm water at 40° C. for 216 hours, the water on the surface was wiped off with a paper wiper, and then the coating was naturally dried at 25° C. for 10 minutes, and the anti-fogging properties were evaluated. [Moisture resistance] Each of the coatings was left to stand for 24 hours in a thermohygrostat (KCL-2000W, Tokyo Rikakikai Co., Ltd.) set at 50° C. and 98% RH, and then naturally dried at 25° C. for 10 minutes, and the antifogging properties were evaluated.

[0082] [Table 1]

[0083] [Table 2]

[0084] As shown in Tables 1 and 2, the coatings of Examples 3-1 to 3-5 and Examples 4-1 to 4-5 maintain excellent anti-fogging properties even after hot water resistance tests (24-hour immersion, 240-hour immersion) and moisture resistance tests (50°C, 98% RH, 24 hours). In particular, the coating of Example 3-1 is found to have excellent durability. On the other hand, in the coatings of Comparative Examples 3-1, 3-2, 3-4, 4-1, 4-2, and 4-4, the anti-fogging properties were lost after immersion in hot water for 24 hours, and in the coatings of Comparative Examples 3-3 and 4-3, the anti-fogging properties were lost after immersion in hot water for 240 hours, indicating that these coatings have poor water resistance.

Claims

1. A hydrophilic copolymer comprising a structural unit (a) represented by the following formula (1) and a structural unit (b) represented by the following formula (2), wherein the content of the structural unit (a) is 50 to 99% by mass, and the content of the structural unit (b) is 1 to 20% by mass. 【Chemistry 1】 (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; X 1 represents a divalent linking group, In formula (2), R 3 represents a hydrogen atom or a methyl group, R 4 and R 5 each independently represents an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 10 carbon atoms; X 2 represents a divalent linking group, n represents an integer of 1 to 3, and an asterisk * indicates a bond to an adjacent structural unit.

2. The X 1 and X 2 2. The hydrophilic copolymer according to claim 1, wherein each of the groups independently represents a divalent linking group having at least one bond selected from the group consisting of a urethane bond, a urea bond, a thiourethane bond and a thiourea bond.

3. A hydrophilic composition comprising the hydrophilic copolymer according to claim 1 or 2.

4. A coating formed by curing the hydrophilic composition according to claim 3.

Citation Information

Patent Citations

  • Hydrophilic super-lubricious coating and activation-free coated urinary catheter

    CN109337492A

  • Surface treatment agent composition, surface treatment method, surface treatment substrate, copolymer, and its production method

    JP2012031247A

  • Surface coated powder processed with cationic (METH)acrylic silicone-based graft copolymers, and powder dispersed compositions and cosmetics containing the same

    JP2014074088A

  • Hydrophilic copolymer, and thermosetting composition and coating film containing the hydrophilic copolymer

    JP2018162431A

  • Surface modifier

    WO2011162225A1